UNITED NATIONS CONTRIBUTION TO FAMILIES (FOCUS ON FAMILY INTERNATIONAL DAY) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The International Family Day on May 15 has been proclaimed by the United Nations since 1993 and since then it has been celebrated all over the world. This day provides an opportunity to promote awareness of family issues and to increase knowledge about social, economic and demographic processes affecting families.The importance the United Nations gives to the family by marking this day shows that despite the many transformations of families over the past years in terms of their structure and functions, the family is still recognized as a founded unit / cell of society. The interest of this organization for the family as a community and its well-being began in the early eighties. In 1983, on the basis of the recommendations of the Economic and Social Council, the Commission for Social Development, in its Resolution on the role of the family in the development process (1983/23), requested the Secretary-General to raise awareness among decision-makers and the public on the problems; the needs of the family. Thus, the United Nations is beginning to focus on family issues.This paper reviews the topics under which the International Family Day has been celebrated over the years, as well as the issues that have been relevant in the given period. Similarly, the purpose of this paper is to explore the dynamics of issues related to families that the United Nations considers important.